Power matters : The end of innocence in adult education program planning - Arthur L. Wilson; Thomas Sork; Elizabeth J. Tisdell; Ronald M. Cervero (Adult Education Research Conference, 1996)
The purpose of this symposium is to make public the crucial debate about our political and ethical responsibilities as adult education curriculum and program planners. Knowledge, Power, and Identity : Planning Theory’s Construct of Adult Education Practice (Arthur L. Wilson) Of Babies and Bathwater : A Friendly Critique of Conventional Planning Theory (Thomas J. SorkThe Politics of ‘Inclusivity’ in Curriculum and Program Planning (Elizabeth J. Tisdell) Beyond Innocence in Program Planning : Our Issues and Responsibilities in Graduate Education (Ronald M. Cervero)